Emotional intelligence as a predictor of identified regulation, introjected regulation, and external regulation in athletes - Mercader-Rubio, Isabel; Ángel, Nieves Gutiérrez; Ruiz, Nieves Fátima Oropesa; Carrión-Martínez, José Juan (Frontiers in Psychology, 2022)
Self-determination theory (SDT) considers motivation as a multidimensional phenomenon, with different levels of intensity, purposes, intentions, wills, and autonomies. It distinguishes between intrinsic motivation (IM), extrinsic motivation (EM) and amotivation (AM). In this paper we are going to focus on extrinsic motivation, which is related to those tasks that the subject performs without having a purpose in themselves, and which is composed of identified regulation, introjected regulation, and external regulation. The aim of this research is to analyze the relationship between them and emotional intelligence in 165 students of university degrees related to Physical Activity and Sport Sciences. The main findings of this work lie mainly in the demonstration of the fact that emotional intelligence is a predictor of identified regulation, introjected regulation, and external regulation.